The semiotic analysis on the inheritance of Chinese cultural symbols from Ne Zha conquers the Dragon King (1979) to Ne Zha: birth of The Demon Child (2019) - Wang, Yingli; Mohd Sharif, Nadzri; Mohammad Noh, Liza Marziana (Universiti Teknologi MARA, Perak, 2025)
This paper takes Nezha Conquers the Dragon King in 1979 and Nezha: Birth of the Demon Child in 2019 as the research objects to explore the inheritance of Chinese cultural symbols in the field of animation. Through qualitative research, it is found that with the same story source, core elements such as the image of Nezha and his magic weapons construct the foundation of cultural inheritance. The spirit of resistance, as the spiritual connotation of cultural symbols, shows the continuations between traditional justice and modern struggle against fate in different eras. In terms of the application of traditional elements, Nezha Conquers the Dragon King adheres to the aesthetics of traditional painting, while Nezha: Birth of the Demon Child innovatively integrates traditional and modern technologies. This indicates that the inheritance of cultural symbols requires adhering to the core and adapting to the changes of the times. In the context of globalization, animation creators should draw on these experiences to promote the inheritance and innovation of Chinese cultural symbols, and contribute to the dissemination of Chinese culture and the development of world cultural diversity.